Mechanism-based inhibition of CYPs and RMs-induced hepatoxicity by rutaecarpine. (2nd November 2015) - Zhang, Fang-Liang; He, Xin; Zhai, Yi-Ran; He, Li-Na; Zhang, Si-Chao; Wang, Li-Li; Yang, Ai-Hong; An, Li-Jun
Abstract: 1. Rutaecarpine, a quinolone alkaloid isolated from the unripe fruit of Evodia rutaecarpa, is one of the main active components used in a variety of clinical applications, including the treatment of hypertension and arrhythmia. However, its hepatotoxicity has also been reported in recent years. 2. Reactive metabolites (RMs) play a vital role in drug-induced liver injury. Rutaecarpine has a secondary amine structure that may be activated to RMs. The aim of the study was to investigate the inhibition of rutaecarpine on CYPs and explore the possible relationship between RMs and potential hepatotoxicity. 3. A cell counting kit-8 cytotoxicity assay indicated that rutaecarpine can decrease the primary rat hepatocyte viability, increase lactate dehydrogenase and reactive oxygen species, reduce JC-1, and cause cell stress and membrane damage. The indexes were significantly restored by adding ABT, an inhibitor of CYPs. A cocktail assay showed that CYP1A2, CYP2C9, CYP2C19, CYP2E1 and CYP3A4 can be inhibited by rutaecarpine in human liver microsomes. The IC50 values of CYP1A2 with and without NADPH were 2.2 and 7.4 μM, respectively, which presented a 3.3 shift. The results from a metabolic assay indicated that three mono -hydroxylated metabolites and two di -hydroxylated metabolites were identified and two GSH conjugates were also trapped. 4. Rutaecarpine can inhibit the activities of CYPs and exhibit a potential mechanism-based inhibition on CYP1A2. RMs may cause herb–drug interactions, providing important information for predicting drug-induced hepatotoxicity.